A sustainability practices educational intervention in response to environmental matters of concern amongst Makhanda youth - Musiyiwa, Fungayi Lona (Rhodes University, Faculty of Education, Department of Environmental Learning Research Centre)
This study responded to urbanisation as one of the challenges affecting youths' lifestyles in this century. Children and youth around the world are living in overpopulated, polluted and unsafe environments which fail to produce opportunities for learning, play and recreation (World Health Organisation [WHO], 2017). This study explored these issues in the context of Makhanda with an intervention to engage youth in sustainability practices, to help them to strengthen sustainable lifestyles. The participants in this research were members of two eco-clubs from two schools in Makhanda ranging in age from 12-14 years (primary school) and 15-17 years (high school). The study explored how learning processes within a club intervention contributed to the well- being of participating youth and their capacity to live sustainable and fulfilling lives. The research explored (with participants) eight themes as matters of concern namely, 'education', 'home-life', 'energy use', 'mobility', 'leisure and communication', 'waste', 'water' and 'food'. Detailed case narratives exploring Wals' social learning stages were used to explore the themes. These themes were explored through photo narratives of the youths' lives and matters of concern in sustainability issues, risks and practices emanating from the Makhanda context. The pedagogical framework for the intervention was guided by Wals' social learning framework for mobilizing sustainability practices. Social learning interaction took place through all the stages of the framework and the challenges and potentials of the educational intervention were explored in relation to each stage. From the six themes suggested above the youth chose food and water as themes to take forward as a response project. The project pursued was a vegetable garden in which the youth were actively engaged in order to seek and try out sustainable ways of living. An interpretive approach was used within the interpretive paradigm. Qualitative data were generated through focus group discussions, observations, individual interviews and document analysis. Practice architectures theory was used analytically to explore the dynamics of the emergent sustainability practices initiated by the eco-club youth. I used it as a change method and a tool for initiating social learning actions for 'sustainability practices' projects. The study indicated that the youth's key challenges affecting sustainability of their lifestyles are: lack of access to basic infrastructure, recreational facilities, electricity supply, transport, security and water. In this study, it was clear that much of the youth's involvement in these matters of concern and sustainability issues was at the level of participating in the six themes through Wals' social learning processes. This allowed youths to develop their knowledge and skills on how to participate in the gardening project rather than simply focusing on the environmental matters of concern in question. The Handprint Resource Books have been designed for educators who are looking for practical ideas to work with in the learning areas of the National Curriculum. The focus is on sustainability practices that can be taken up within the perspective that each learning area brings to environment and sustainability concerns. The use of the Handprint Resource Books promoted active youth participation and interaction encouraging youth to be reflective thinkers, which led to understanding of the issues and the sustainability practices that emerged during the discussions. The Handprint Resource Books focused on sustainability practices within the learning area of environment and sustainability concerns. Due to her facilitation skills, an environmental expert's presentation on a sustainability topic enabled youths to select the intended project. The involvement of youth in the implementation of the vegetable garden as a sustainability practice empowered youth to be more confident in engaging in a collective action for change as they developed the capability to share and start their own vegetable gardens at their homes.
Keywords: Sustainable living -- South Africa -- Makhanda; Social learning -- South Africa -- Makhanda; Eco clubs -- South Africa -- Makhanda; Environmental education -- Activity programs -- South Africa -- Makhanda; Youth in development -- South Africa -- Makhanda; Youth -- Social conditions